Diferentes níveis protéicos na dieta de girinos de rã-touro (Lithobates catesbeianus) e seus efeitos sobre o tecido hepático - Mansano, Cleber F.M. [UNESP]; Pereira, Marcelo M. [UNESP]; Macente, Beatrice I. [UNESP]; Makino, Lilian C. [UNESP]; Jacintho, Ana P.P. [UNESP]; Nakaghi, Laura S.O. [UNESP]; De Stéfani, Marta V. [UNESP] (FapUNIFESP (SciELO), 2016)
To verify the occurrence of liver morphological changes, bullfrog tadpoles were fed three diets: An experimental diet with 32.68% crude protein and two commercial diets with 37.92% and 57.53% crude protein. Tadpoles were distributed into a completely randomized design (CRD) with three treatments and four replications. Liver samples were collected twice, on the 30th and 60th day of the experiment. Tadpole livers were fixed in Bouin's solution, then subjected to routine histotechnology procedures, and stained with hematoxylin - eosin (HE). Microscopic evaluation of liver tissue showed several morphological changes like disorganization and vacuolization of hepatocytes; periportal, multifocal and diffuse mononuclear inflammatory infiltrate, eosinophilic inflammatory infiltration, congestion, hemorrhage, hemolysis and necrosis. The liver changes found in this study suggest that diets used for bullfrog tadpoles, did not meet their dietary needs, what affected their homeostasis, thus compromising their health.
Different protein levels in the diet of bullfrog tadpoles (Lithobates catesbeianus) and its effects on the liver tissue
Keywords: Bullfrog; Commercial diets; Hepatocytes; Lithobates catesbeianus; Liver histology; Liver morphology; Protein